In vitro influence of Theileria annulata on the functions of bovine dendritic cells for stimulation of T lymphocyte proliferation. Issue 1 (10th January 2020) - Rashid, Muhammad; Liu, Junlong; Guan, Guiquan; Wang, Jinming; Li, Zhi; Hassan, Muhammad Adeel; Rashid, Muhammad Imran; Mukhtar, Muhammad Uzair; Luo, Jianxun; Yin, Hong
Abstract: The present study was performed on antigen-presenting cells (APCs) of Theileria annulata transformed dendritic cells (TaDCs) and monocyte-derived dendritic cells (MoDCs) to compare differences in antigen presentation and stimulation of T lymphocyte proliferation. Antigen presentation for T lymphocyte proliferation was analysed by flow cytometry. Additionally, the level of mRNA transcription of small GTPases of the Rab family expressed in the TaDC cell line was analysed by quantitative real-time polymerase chain reaction (Q-RT-PCR). The endocytosis rate of TaDCs was significantly ( P < 0.01) lower than in MoDCs. In contrast, when T lymphocytes were co-cultured with TaDC-APCs T cell proliferation was similar, while co-culture with MoDC-APC stimulated proliferation of CD4 + cells to a greater degree than CD8 + cells. However, the efficacy of TaDC-APCs to stimulate T lymphocytes dropped as the number of passages of TaDC-APC increased. Likewise, the transcription level of Rab family genes also significantly ( P > 0.001) declined with progressive passages (>50) of the TaDC cell line. We conclude that initially the TaDC cell line efficiently presents antigen to stimulate T lymphocyte proliferation to produce a cellular immune response against the presented antigen.